Blood myeloid cells differentiate to lung resident cells and respond to pathogen stimuli in a 3D human tissue-engineered lung model - Roe, Mandi M.; Do, Taylor; Turner, Sean; Jevitt, Allison M.; Chlebicz, Magdalena; White, Karley; Oomens, Antonius G. P.; Rankin, Susannah; Kovats, Susan; Gappa-Fahlenkamp, Heather (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Respiratory infections remain a leading global health concern. Models that recapitulate the cellular complexity of the lower airway of humans will provide important information about how the immune response reflects the interactions between diverse cell types during infection. We developed a 3D human tissue-engineered lung model (3D-HTLM) composed of primary human pulmonary epithelial and endothelial cells with added blood myeloid cells that allows assessment of the innate immune response to respiratory infection. Methods: The 3D-HTLM consists of small airway epithelial cells grown at air-liquid interface layered on fibroblasts within a collagen matrix atop a permeable membrane with pulmonary microvascular endothelial cells layered underneath. After the epithelial and endothelial layers had reached confluency, an enriched blood monocyte population, containing mostly CD14+ monocytes (Mo) with minor subsets of CD1c+ classical dendritic cells (cDC2s), monocyte-derived dendritic cells (Mo-DCs), and CD16+ non-classical monocytes, was added to the endothelial side of the model. Results: Immunofluorescence imaging showed the myeloid cells migrate through and reside within each layer of the model. The myeloid cell subsets adapted to the lung environment in the 3D-HTLM, with increased proportions of the recovered cells expressing lung tissue resident markers CD206, CD169, and CD163 compared with blood myeloid cells, including a population with features of alveolar macrophages. Myeloid subsets recovered from the 3D-HTLM displayed increased expression of HLA-DR and the co-stimulatory markers CD86, CD40, and PDL1. Upon stimulation of the 3D-HTLM with the toll-like receptor 4 (TLR4) agonist bacterial lipopolysaccharide (LPS), the CD31+ endothelial cells increased expression of ICAM-1 and the production of IL-10 and TNFα was dependent on the presence of myeloid cells. Challenge with respiratory syncytial virus (RSV) led to increased expression of macrophage activation and antiviral pathway genes by cells in the 3D-HTLM. Discussion: The 3D-HTLM provides a lower airway environment that promotes differentiation of blood myeloid cells into lung tissue resident cells and enables the study of respiratory infection in a physiological cellular context.